Accountability of Tri Hita Karana's Cultural Perspective in Socio-religious Organization - Rina, Ni Made Dwi; Sujana, I Ketut; Sudana, I Putu; Wirajaya, I Gde Ary (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 17 No 2 (2022)DO - 10.24843/JIAB.2022.v17.i02.p08, 2022)
This study aims to gain an understanding of social reality through inductive thinking based on the experiences of the informants on actions and the meaning of accountability in the cultural perspective of Tri Hita Karana at the Sagraha Mandra Kantha Santhi Foundation. The methodology of this research is descriptive interpretive with the approach of Interpretative Phenomenological Analysis (IPA). Qualitative data was collected by conducting observations, in-depth interviews and documentation. The findings indicate that the Sagraha Mandra Kantha Santhi Foundation is accountable to God (parahyangan), to others (pawongan) and to the environment (palemahan). The analysis also shows that there are three themes that emerge from the meaning of the experience of the informants in the cultural perspective of Tri Hita Karana, namely sincere offerings, economic contributions to society, and protecting the environment.